2019
DOI: 10.1021/acsanm.9b01767
|View full text |Cite
|
Sign up to set email alerts
|

Water-Repellent Surfaces Consisting of Nanowires on Micropyramidal Structures

Abstract: Super-repellent surfaces are relevant for several practical applications, such as water collection and self-cleaning and anti-icing surfaces. However, designing surfaces that can maintain their super-repellency when the surface is subjected to a humid environment is still a challenge. Here, we present a two-tier roughness surface consisting of nanowires on micro-pyramidal structures. We compare the wetting properties of this surface with other single-level roughness surfaces and surfaces with nanowires on micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Smaller droplet departure diameter and higher droplet departure frequency on the SAM-coated plain surface were reported compared to the nanotextured surface by Zhong et al which was attributed to condensate and surface interfacial interactions. A comparative study between a two-tier roughness surface consisting of nanowires on micropyramids and single-level structured surfaces for condensation under the ambient condition showed that the two-tier surface with nanowires on micropyramids yielded superior droplet mobility under both wet (condensation) and dry conditions . Due to the structures on micropyramids of the two-tier surface, droplets showed lower adhesion to the pyramid side, and the transition from the Cassie to Wenzel state was avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller droplet departure diameter and higher droplet departure frequency on the SAM-coated plain surface were reported compared to the nanotextured surface by Zhong et al which was attributed to condensate and surface interfacial interactions. A comparative study between a two-tier roughness surface consisting of nanowires on micropyramids and single-level structured surfaces for condensation under the ambient condition showed that the two-tier surface with nanowires on micropyramids yielded superior droplet mobility under both wet (condensation) and dry conditions . Due to the structures on micropyramids of the two-tier surface, droplets showed lower adhesion to the pyramid side, and the transition from the Cassie to Wenzel state was avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, after humid treatment, the CA of MoS 2 –Cu 2 O coating changed from ∼164 to 152°. This is due to the extra adhesion produced by the liquid already existing below the water droplet. , On a dry surface of MoS 2 nanosheet–Cu 2 O nanoparticle coating, a water droplet may remain in the Cassie state, but during condensation conditions, vapors are nucleated in the grooves of MoS 2 nanosheet–Cu 2 O nanoparticle coating. Subsequently, when a water droplet is deposited on this surface, the water droplet combines with the nucleated vapor.…”
Section: Resultsmentioning
confidence: 99%
“…The shape of the microcone was reported by Sharma et al (Figure c1) and Zhang et al (Figure d), and the cone array was reported by Zhao et al (Figure a1). The columnar graded surfaces reported by Vandadi et al (Figure b1) all promoted droplet coalescence jumping by the spontaneous dewetting transition of condensate droplets. During the growth process of droplets at the bottom of the structure, the droplets were in the Wenzel state or the partial wetting state. The Laplace pressure difference between the upper and lower surfaces of the droplet would cause the droplet to move upward in forming the Cassie state.…”
Section: Effect Of Superhydrophobic Structurementioning
confidence: 91%
“…(d) Oblique view and cross-section view of pyramids with nanowires. Reproduced from ref , copyright 2019, American Chemical Society.…”
Section: Effect Of Superhydrophobic Structurementioning
confidence: 99%